The experimental method for testing a non-Abelian dark matter model - Dzhunushaliev, V.D.; Protsenko, N.А. (Recent Contributions to Physics, 2018)
A method of experimental verifcation of non - Abelian dark matter model where the dark matter is a classic non-Abelian SU (3) gauge field Yang - Mills is proposed. The method is based on the analysis of motion of charged particles in the colored non - Abelian gauge field. For the analysis of the motion we use Wong equations that are the generalization of the second Newton law for particles with a color charge. The field strengths values were evaluated in the colored electric field in the galaxy. A mechanism for cutting off classical gauge fields in space is considered, taking into account quantum effects. The value of the strength, as well as the potential of the colored electric field in the galaxy, is estimated. A solution of the Wong equations describing the motion of a color charge in a non-Abelian model of dark matter is obtained. On this basis, a method is proposed for experimental verification of a non-Abelian model of dark matter.
Keywords: dark matter, Yang – Mills equations, colored particles, non – Abelian gauge field